ALTERNATIF UPAYA KETAHANAN PELAKU HOME-BASED ENTERPRISES (HBE) BATIK PADA MASA PANDEMI COVID-19 DI KAMPUNG BATIK SEMARANG - Bintara Yudha Mustaidz Billah; Samsul Ma'rif (Jurnal Riptek, 2021)
The Covid-19 outbreak has had an impact on the national and international economic sectors. Various problems that arise, one of which is in the Micro, Small, Medium Enterprises (MSME) sector due to a decline in buyer demand, supply constraints, and export orders that can cause businesses to run into a deficit. Whereas MSMEs absorb workers up to 90% on a national scale and the informal sector plays a role in the movement of the national economy up to 60%. Thus, a strategy is needed by business actors in an effort to survive Home-Based Business (HBE) / home-based MSMEs during the Covid-19 pandemic in Kampung Batik Semarang. The method used in this research is descriptive quantitative analysis with primary and secondary data collection. The Sustainable Livelihood Approach (SLA) approach as an introduction to describe the conditions of batik HBE during the Covid-19 pandemic and to support subsequent analysis to obtain results in the form of alternative efforts to resilience for batik HBE actors during the Covid-19 pandemic using the Analytical Hierarchy Process (AHP) analysis method. In this study, the condition of HBE was explained and with AHP analysis, the highest weight was obtained, namely by carrying out a digital marketing strategy of 24%, which means that it is the main alternative in efforts to maintain batik HBE during the Covid-19 pandemic. Furthermore, the second highest weight is promotion with a weight of 22.4%, followed by product lines at 21.2%, then taking action at 19.1%, and business consolidation is in the last rank at 13.3%. This research can be a recommendation to the Semarang City Government in making policies related to the development of MSMEs.